Determination of the rolling resistance of roller skis. (March 2017) - Schindelwig, Kurt; Mössner, Martin; Hasler, Michael; Nachbauer, Werner
The rolling resistance of skis used in roller skiing competitions should resemble the gliding resistance of cross-country skis to allow specific training and moving patterns for cross-country skiing and to guarantee equal opportunities for athletes in roller ski races. Therefore, the purpose of this work was to develop a portable rolling resistance meter to precisely measure the rolling resistance of roller skis. Measurements were based on recordings of the angular deceleration of a flywheel due to the rolling resistance between a roller ski's wheel and the flywheel's steel surface. Rolling resistance coefficients of four roller ski types ranged between 0.019 and 0.025. Measurements of the rolling resistance coefficient showed a precision of 1.26%. Substantial rolling resistance coefficient variations (10%) were observed for wheels of the same type. Furthermore, the rolling resistance coefficient was found to be negatively correlated with normal load or ambient temperature. The proposed rolling resistance meter is appropriate to determine the rolling resistance coefficient of roller skis' wheels precisely.